Ethical Credibility Over Doctrinal Supremacy: Nurcholish Madjid's Framework for Managing Intra-Muslim Tension in an Urban Indonesian Community - Fauzan Akbar Novianto; Fuad Nawawi; Indra Gunawan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2025)
This study shifts the focus of religious moderation discourse from abstract interfaith conflict to subtle intra-Muslim fragmentation at the grassroots level. Centered on the case of Teratai Putih, East Jakarta, it explores the symbolic boundaries and doctrinal tensions between two mosques representing traditionalist and reformist orientations. Employing a qualitative case study through interviews, field observations, and document analysis, the research applies Nurcholish Madjid’s framework to analyze how ethical substance overrides formalistic piety in shaping communal trust. The findings reveal a critical anomaly: worshippers transcend theological divisions to contribute zakat and donations to institutions that demonstrate higher ethical credibility and transparent management. This phenomenon affirms that Ethical Credibility has surpassed Doctrinal Supremacy as the primary currency of communal trust. Conceptually, the study advances the paradigm of religious moderation by redefining legitimacy from Creed Legitimacy to Credibility Legitimacy, resonating with Madjid’s vision of an inclusive and ethically grounded Islamic community.